Experimental Study on the Failure Mechanism of Finned Pile Foundation under Horizontal Cyclic Loads - Lunliang Duan; Meiling Fan; Bolin Zhan; Haicui Wang; Haiming Liu; Guangwu Tang; Bo Geng (Buildings)
In order to study the failure mechanism of a finned pile foundation under horizontal cyclic loads, a physical model test of the pile–soil interaction of finned pile is designed in this paper. Based on the model tests, the pile top displacement, the cyclic stiffness of the pile foundation, and the response of pore water pressure within the soil around the pile were fully studied for the finned pile foundation under horizontal cyclic loads. It is found that the cyclic stiffness attenuation of the finned pile foundation is more severe than that of a regular single pile foundation, but the final stiffness at equilibrium is still greater than that of a regular single pile foundation. The accumulation of horizontal displacement at the pile top and pore water pressure within the soil around the pile mainly occurs in the first 1000 loading cycles, and an increase in fin plate size will reduce the magnitude of pore water pressure and pile top displacement. This study can not only deepen the understanding of the failure mechanism of finned pile foundation under horizontal cyclic loads, but also provide guidance for the design of the finned pile foundation.